HOW FAR ARE THE CZECH REPUBLIC AND SLOVAKIA FROM OPTIMAL TAXATION? QUANTITATIVE ANALYSIS BASED ON THE LAFFER CURVE - Malik, Jakub; Poliakova, Adela (Veredas do Direito, 2026)
The aim of this article is to analyze the relationship between the corporate income tax rate and net tax revenues in Slovakia and the Czech Republic using the Laffer curve concept. Based on data on actual tax revenues and their discounting to net present value, a quadratic regression analysis was created that takes into account the assumed parabolic relationship between the tax rate and tax revenues. The optimal tax rate was identified as approximately 17.64% for Slovakia and 26.12% for the Czech Republic. The results confirm the nonlinear nature of the relationship and suggest that excessive tax increases can reduce business motivation, encourage tax optimization, and threaten the competitiveness of the economy. The analysis emphasizes the importance of optimizing tax policy not only to maximize government revenues, but also to support investment and long-term sustainable economic growth.